2016
DOI: 10.3201/eid2203.141971
|View full text |Cite
|
Sign up to set email alerts
|

Use of Transnational Services to Prevent Treatment Interruption in Tuberculosis-Infected Persons Who Leave the United States

Abstract: Scale up of such services is possible and encouraged because of potential health gains and reduced healthcare costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…O tratamento da tuberculose resistente torna-se mais oneroso, além de registrar maior número de óbitos. Por isso, o crescente aumento do número de casos, apesar da luta contra a doença, tem preocupado os países globalmente (TSCHAMPL CA et al,2016).…”
Section: Discussionunclassified
“…O tratamento da tuberculose resistente torna-se mais oneroso, além de registrar maior número de óbitos. Por isso, o crescente aumento do número de casos, apesar da luta contra a doença, tem preocupado os países globalmente (TSCHAMPL CA et al,2016).…”
Section: Discussionunclassified
“…Within Europe, the European Respiratory Society and the WHO Regional Office for Europe have also jointly developed a web-based, open-access multi-lingual system, TB Consilium, with a function to introduce a patient to a treatment provider in another country [ 19 ]. The United States Cure TB Program, which is a federally funded program by San Diego TB Control Program and now an official partner with the Center for Disease Prevention and Control, has been systematically providing binational United States and Mexico) referral services since 1997, and has recently expanded their program to cover the rest of the world [ 20 , 21 ]. Another non-profit organization, Migrant Clinicians Network, has also been serving mobile patients with health needs since 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Their services include transfer of medical records, follow-up and other patient support, and as for TB, has consistently reported treatment completion rate of more than 84% [ 22 ]. Furthermore, a recent modelling study has indicated that a scale-up of these cross-border referral services would not only benefit the patients themselves, but also the Unites States directly, as well as the international community at large [ 20 ]. Results of our study indicate that such a cross-border referral system is necessary in Japan too–a small pilot project with countries with relatively large number of returning patients, such as China, the Philippines and Vietnam, may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…A TB patient who crosses the United States-Mexico border often requires TB program staff members to conduct activities above and beyond what is normally done for a non-bordercrossing TB patient, such as locating contacts who may be frequent border crossers and, therefore, are difficult to find and working with binational programs and TB control program staff members in Mexico to ensure follow-up and treatment completion of patients who reside in, move to, or frequently travel to Mexico. 6,17 Some TB patients in Mexico who do not cross the border into the United States will meet the surveillance definition for binational cases of TB if their treatment is coordinated or supplied by a US-funded, binational TB program. For example, Grupo Sin Fronteras, a federal-and state-funded, binational TB program in Harlingen, Texas, treats patients in Mexico who have not crossed the border to the United States.…”
Section: Discussionmentioning
confidence: 99%
“…A TB patient who crosses the United States–Mexico border often requires TB program staff members to conduct activities above and beyond what is normally done for a non–border-crossing TB patient, such as locating contacts who may be frequent border crossers and, therefore, are difficult to find and working with binational programs and TB control program staff members in Mexico to ensure follow-up and treatment completion of patients who reside in, move to, or frequently travel to Mexico. 6,17…”
Section: Discussionmentioning
confidence: 99%